Implementasi Metode Lean Six Sigma dalam Meningkatkan Efisiensi Proses Produksi pada Industri Kayu CV. Jaya Abadi - Muhammad Ferdiansa; Ahkmad Wasiur Rizqi; Moh. Jufriyanto (G-Tech: Jurnal Teknologi Terapan, 2024)
Cv.Jaya Abadi is a company engaged in wood production. During the wood production process there are several types of defects, namely ring shake defects, holes and knots. Apart from that, in every production process there are waste activities or non-value added activities (NVA). During the research period it was discovered that the average number of defective products was 8.95%, this could reduce company profits. This research applies the concept of quality control with the Lean Six Sigma approach in an effort to increase company efficiency. The research results show that the total cycle time is 5876.40 minutes with a lead time of 16625.80 minutes. It is known that the NVA activity is 40.89%. In the research period, the average DPMO value was found to be 29835.39 or 3.39 sigma level. The largest defect is dominated by the ring shake defect type, FMEA analysis shows that the method factor has the largest RPN value so that corrective action needs to be taken in the use of wood protection by creating a new wood storage warehouse, applying additional protection, careful handling during the wood production process, and carry out regular monitoring.